2009
DOI: 10.1103/physrevb.79.094411
|View full text |Cite
|
Sign up to set email alerts
|

Complex magnetism of iron monolayers on hexagonal transition metal surfaces from first principles

Abstract: Using first-principles calculations, we demonstrate that an Fe monolayer can assume very different magnetic phases on hcp ͑0001͒ and fcc ͑111͒ surfaces of 4d-and 5d-transition metals. Due to the substrates' d-band filling, the nearest-neighbor exchange coupling of Fe changes gradually from antiferromagnetic ͑AFM͒ for Fe films on Tc, Re, Ru, and Os to ferromagnetic on Rh, Ir, Pd, and Pt. In combination with the topological frustration on the triangular lattice of these surfaces the AFM coupling results in a 120… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

11
88
0

Year Published

2009
2009
2024
2024

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 75 publications
(99 citation statements)
references
References 26 publications
11
88
0
Order By: Relevance
“…For the FCC(001) substrates we find that the d interlayer distance is fairly constant, and the absolute value of δ increases with increasing a. Concomitantly, the spin magnetic moment of Fe monotonically increases from Ir towards Au due to the increasing dband filling of the substrate [8].…”
Section: Geometrical Structure and Magnetic Momentsmentioning
confidence: 70%
See 1 more Smart Citation
“…For the FCC(001) substrates we find that the d interlayer distance is fairly constant, and the absolute value of δ increases with increasing a. Concomitantly, the spin magnetic moment of Fe monotonically increases from Ir towards Au due to the increasing dband filling of the substrate [8].…”
Section: Geometrical Structure and Magnetic Momentsmentioning
confidence: 70%
“…Another mechanism that can affect the magnetic ordering of a monolayer is the hybridization between the monolayer and the substrate. Hardrat et al demonstrated the change of the exchange coupling and the magnetic ordering of an Fe ML on HCP(0001) and FCC(111) surfaces of 4d and 5d transition metals due to the change in d-band filling [8]. When increasing the atomic number of the substrate element, the d-band of the substrate moves downwards with respect to the Fermi level while the energetic position of the Fe 3d band remains roughly unchanged.…”
Section: Introductionmentioning
confidence: 99%
“…4 can be understood on the basis of the hybridization of Fe 3d states with Ir 5d states and Pd 4d states. First-principles calculations show that the NN exchange interaction in a hexagonal Fe ML depends on the 4d or 5d band filling of the substrate and can be tuned from ferro-to antiferromagnetic 33 . On the (111) surface of Ir, which has one electron less in the d band than Pd, the NN exchange is still ferromagnetic but reduced significantly with respect to Fe/Pd(111) (J 1 ¼ 5.7 versus 23.3 meV).…”
Section: Resultsmentioning
confidence: 99%
“…49 Also, frustration effects, like on Rh(111) surfaces, could lead to interesting magnetic structures. 50 From the LDOS it can be seen how hybridization affects the magnetic order in these systems: Compared to Ag or Pd(100) substrates, the broadening of the d band is enhanced, leading to a tendency in favor of AFM ordering for Fe but FM for Cr. Calculations of the magnetic anisotropy showed that only V and Cr monolayers on Rh(100) have an out-of-plane easy axis in their ground state, while the magnetization of Mn, Fe, Co, and Ni is oriented in plane.…”
Section: Discussionmentioning
confidence: 99%